Stepping forward on shaky ground: developing equity-centered principals in politically complex settings - Lewis-Durham, Tiffanie; Bradford, Kelly; Hernandez, Paula; Clarida, Brian (Frontiers in Education, 2025)
IntroductionLarge urban districts across the country have tried to establish programs or partnerships that would ensure a pipeline of high-quality equity-centered school leaders. However, dubious, and sometimes hostile political contexts have often made these endeavors uncertain.MethodsIn this critical discourse analysis, we examine the contexts that frame the role of leadership pipelines in North Carolina, a state where the legislature has introduced several measures to diminish educational equity efforts along the K-16 spectrum.ResultsWe find that the unsettled nature of a legal case, Leandro v. North Carolina State Board of Education, has helped to create an atmosphere of low certainty and that competing definitions of equity frame the role and necessity of leadership pipelines.DiscussionOur findings offer important insights into the challenge of undertaking equity-centered reform in politically complex settings.